2021
DOI: 10.1016/j.omto.2021.07.014
|View full text |Cite
|
Sign up to set email alerts
|

Systemic delivery of TNF-armed myxoma virus plus immune checkpoint inhibitor eliminates lung metastatic mouse osteosarcoma

Abstract: Solid cancers that metastasize to the lungs represent a major therapeutic challenge. Current treatment paradigms for lung metastases consist of radiation therapy, chemotherapies, and surgical resection, but there is no single treatment or combination that is effective for all tumor types. To address this, oncolytic myxoma virus (MYXV) engineered to express human tumor necrosis factor (vMyx-hTNF) was tested after systemic administration in an immunocompetent mouse K7M2-Luc lung metastatic osteosarcoma model. Vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
36
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(38 citation statements)
references
References 58 publications
2
36
0
Order By: Relevance
“…For example, a live attenuated ZIKV vaccine candidate and a recombinant orthopoxvirus (CF33) oncolytic activity was enhanced by immunotherapy [ 118 , 119 ]. Oncolytic HSV-1 (ONCR-177), adenovirus (TILT-123), and MYXV (vMyx-hTNF) expressing single or multiple immune stimulatory cytokines enhanced oncolytic activity when combined with ICIs [ 120 , 121 , 122 ].…”
Section: Combination Therapy With Oncolytic Virusmentioning
confidence: 99%
“…For example, a live attenuated ZIKV vaccine candidate and a recombinant orthopoxvirus (CF33) oncolytic activity was enhanced by immunotherapy [ 118 , 119 ]. Oncolytic HSV-1 (ONCR-177), adenovirus (TILT-123), and MYXV (vMyx-hTNF) expressing single or multiple immune stimulatory cytokines enhanced oncolytic activity when combined with ICIs [ 120 , 121 , 122 ].…”
Section: Combination Therapy With Oncolytic Virusmentioning
confidence: 99%
“…Previous studies using the K7M2 lung metastatic osteosarcoma model have shown that immune checkpoint inhibitors anti-PD-L1 and anti-CTLA-4 are efficacious when treatment is initiated very early after tumor seeding [ 11 , 12 ]. However, these immunotherapies lose efficacy when used in later-stage disease [ 13 ]. One way to improve and complement immunotherapy is to combine ICIs with an oncolytic virus [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Oncolytic virotherapy, on the whole, is currently exploring questions based around the genetic arming of the virus, and how to effectively deliver the virus to metastatic sites of tumors that are not amenable to direct intratumoral injection delivery [ 15 , 16 ]. One virus being studied both for optimal design, through transgene arming, and for systemic delivery to hard-to-reach cancer is oncolytic myxoma virus (MYXV) [ 13 , 17 , 18 ]. MYXV is a member of the poxvirus family poxviridae , and the genus leporipoxvirus [ 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations